Sociodemographic Determinants for Oral Health Risk Profiles - J. Vanobbergen; L. De Visschere; M. Daems; A. Ceuppens; J. Van Emelen (International Journal of Dentistry)
The present study aimed to explore the association between caries risk profiles and different sociodemographic factors . The study sample (𝑛=104) was randomly selected within an urban population in Flanders, Belgium. Caries risk was assessed by anamnesis, clinical examination, salivary tests, and a questionnaire. Age, gender, and socio-economic status were extracted from social insurance data files. Social indicators were “occupational status,” “being entitled to the increased allowance for health care interventions” and having access to the “Maximum Bill” (MAF), initiatives undertaken to protect deprived families. In the bivariate analysis there were significant differences in risk profiles between occupational groups (𝑃<.001), between entitled and non-entitled individuals to the increased allowance (𝑃=.02), and between access or no-access to the MAF (𝑃<.01). The multiple logistic model showed a significantly higher chance of being in the low risk group for individuals with no-access to the MAF compared to those with access (OR:14.33–95% C.I. 2.14–95.84).